2018
DOI: 10.3233/rnn-180815
|View full text |Cite
|
Sign up to set email alerts
|

Recovery from apraxic deficits and its neural correlate

Abstract: Background and Objective: Apraxia is a deficit of motor cognition leading to difficulties in actual tool use, imitation of gestures, and pantomiming object use. To date, little data exist regarding the recovery from apraxic deficits after stroke, and no statistical lesion mapping study investigated the neural correlate of recovery from apraxia. Accordingly, we here examined recovery from apraxic deficits, differential associations of apraxia task (imitation vs. pantomime) and effector (bucco-facial vs. limb ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
2
6
0
Order By: Relevance
“…Thus, it can be hypothesized that the insula acts as an integrator for oral praxis, between its verbal and non-verbal components, so that its lesioning mostly associates with co-occurring SA and OA. A similar hypothesis was also proposed by Kusch (Kusch et al 2018 ), who found that limb-apractic patients with insular lesions had a better prognosis than those with lesions in core lesions of the frontoparietal network. From this point of view, our results suggest that frontal regions (in particular precentral gyrus and SLF) may be exclusively responsible for the verbal component of oral praxis—i.e.…”
Section: Discussionsupporting
confidence: 78%
“…Thus, it can be hypothesized that the insula acts as an integrator for oral praxis, between its verbal and non-verbal components, so that its lesioning mostly associates with co-occurring SA and OA. A similar hypothesis was also proposed by Kusch (Kusch et al 2018 ), who found that limb-apractic patients with insular lesions had a better prognosis than those with lesions in core lesions of the frontoparietal network. From this point of view, our results suggest that frontal regions (in particular precentral gyrus and SLF) may be exclusively responsible for the verbal component of oral praxis—i.e.…”
Section: Discussionsupporting
confidence: 78%
“…Furthermore, we examined the actual object use of the ipsilesional left hand with five single objects (hammer, toothbrush, pair of scissors, toy gun, and pencil eraser) and two multiple-object tasks (key & padlock, matchbox & candle [ 11 ];). However, in the current sample of stroke patients, object use deficits were rare ( n = 2, see also [ 28 , 29 ]). Note, that the two patients with impaired object use also performed below cut-off in the KAS and were thus classified as apraxic.…”
Section: Methodsmentioning
confidence: 99%
“…Patients had provided written informed consent to participate in the original studies on motor cognition/apraxia ( Ant et al, 2019 , Binder et al, 2017 , Dafsari et al, 2019 , Dovern et al, 2016 , Kusch, Gillessen et al, 2018 , Kusch, Schmidt et al, 2018 ). These studies contributed 156 stroke patients to the current sample.…”
Section: Methodsmentioning
confidence: 99%
“…1 B, cf. also Kusch, Schmidt et al, 2018 , Raade et al, 1991 ), the interaction term was calculated as the difference of the difference between the mean imitation scores for ML bucco-facial vs ML arm/hand gestures and the difference of the mean imitation scores for MF bucco-facial vs MF arm/hand gestures: Interaction term = (ML bucco-facial gestures mean score − ML arm/hand gestures mean score ) − (MF bucco-facial gestures mean score − MF arm/hand gestures mean score ). The resulting interaction score was then entered into an SVR-LSM analysis.…”
Section: Methodsmentioning
confidence: 99%